1990
DOI: 10.1213/00000539-199005000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Epinephrine and Phenylephrine Increase Cardiorespiratory Toxicity of Intravenously Administered Bupivacaine in Rats

Abstract: We studied the effects of epinephrine and phenylephrine on the cardiorespiratory toxicity of intravenously injected bupivacaine in Sprague-Dawley rats. Our data show that both epinephrine and phenylephrine significantly increased cardiorespiratory toxicity of intravenously injected bupivacaine (P less than 0.007, X2 analyses with Yates' correction). Our data suggest that epinephrine or phenylephrine added to bupivacaine may be more toxic to cardiorespiratory systems than plain bupivacaine or epinephrine alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It does not, however, protect against bupivacaine-induced cardiotoxicity 15 or even potentiate toxicity. 16 This is explained in part by its arrhythmogenic property. Kasten and Martin 17 showed that bretylium, which is an antifibrillatory agent, but not lidocaine, effectively corrected bupivacaine-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…It does not, however, protect against bupivacaine-induced cardiotoxicity 15 or even potentiate toxicity. 16 This is explained in part by its arrhythmogenic property. Kasten and Martin 17 showed that bretylium, which is an antifibrillatory agent, but not lidocaine, effectively corrected bupivacaine-induced cardiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular arrhythmias are associated with acute bupivacaine toxicity, in both isolated cardiac preparations, intact animals and man [12][13][14]. Increased concentrations of circulating plasma catecholamines [15,16] and decreased plasma concentrations of potassium [17] appear to facilitate bupivacaineinduced arrhythmias. Arrhythmias were not the predominant cause of death in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenaline however, increases the myocardial dysfunction caused by bupivacaine overdose by increasing oxygen demand and reentry of arrhythmic cycles. 24 Bupivacaine precipitates rapidly when it is mixed with sodium bicarbonate as it gets less water soluble with an increase in pH. This leads to increased systemic absorption and toxicity.…”
Section: Lidocaine Ideal For Tumescent Liposuctionmentioning
confidence: 99%